Hispanic Review (JSTOR)
Official Web Site: http://hr.pennpress.org The Hispanic Review is a quarterly journal devoted to research in Hispanic literary and cultural studies. Published since 1933 by the Department of Romance Languages at the University of Pennsylvania, the journal features essays and book reviews on the diverse cultural manifestations of Spain and Latin America, from the medieval period to the present.
Keywords: Latin American Studies